Poppy's return - Avi, 1937-; Floca, Brian (New York : HarperTrophy, 2006)
Poppy, her rebellious son, Junior, and his friends Melphitis and Ereth, are summoned back to Gray House, to help save her family home from the destruction of the bulldozer.
4.8
3-6
Keywords: Family problems -- Fiction; Prejudices -- Fiction; Mothers and sons -- Fiction; Mice -- Fiction; Skunks -- Fiction; Porcupines -- Fiction; Family problems -- Fiction; Prejudices -- Fiction; Mother-son relationship -- Fiction; Mice -- Fiction; Skunks -- Fiction; Porcupines -- Fiction